EBUS-TBNA diagnosis of localised amyloidosis presenting as mediastinal lymphadenopathy. Issue 1 (4th December 2018) - Kumar, Avnee; Sivasailam, Barathi; Marciniak, Ellen; Deepak, Janaki
Abstract : Amyloidosis is a unique disease of localised or systemic deposition of the abnormal extracellular fibril. Localised amyloidosis generally takes a benign course, while systemic requires treatment. Adenopathy, especially mediastinal adenopathy, is an unusual manifestation of localised amyloidosis and often requires mediastinoscopy or surgical resection for diagnosis. With the advent of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), there is potential for a less invasive diagnostic approach. We report a rare case of localised mediastinal amyloidosis diagnosed by EBUS-TBNA.